A study on the factors influencing sales in Telekom Malaysia Berhad, Melaka / Shaheda Mat Darus - Mat Darus, Shaheda (Faculty of Business and Management, 2005)
This study is about Business and Sales of Telekom Malaysia Berhad. The purpose of this study is to study several factors that may influence BS's sales. It is also study how to create business opportunity in Melaka with looking at the factors that may influence BS in making decision. Business Sales main function is to market the products and services of Telekom Malaysia such as Direct Exchange Line, Centrex, TM-Automatic Vehicle Location and etc. Business Sales has problem with their sales performance since the competitors such as TIME, Maxis, DiGi and other competitors in Melaka. Business Sales should compete and try to attract customers as many as they can. Besides that, customers also give impact to Business Sales performance. Business Sales has segmented their customers based on size of business. It is difficult to Business Sales create business opportunities in Melaka because nowadays, customers are too wise. Business Sales need to understand and differentiate very well about the customers' needs and behaviors. In addition, price also will give impact to Business Sales performance. The price for all products and services in Business Sales higher than the competitors' price. So that, Business Sales should tell the best reasons to the customers why the price is high. Thus, Business Sales should think the best strategies and the best ways in order to solve all these problems. So that, they will improve their sales performance.